2015
DOI: 10.1186/s12884-015-0554-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the use of magnesium sulphate in pre-eclampsia/eclampsia management in health facilities in Northern Nigeria: a mixed methods study

Abstract: BackgroundEclampsia remains a major cause of perinatal and maternal morbidity and mortality worldwide. We examined facilitators and barriers to the use of magnesium sulphate (MgSO4) in the management of pre-eclampsia/eclampsia (PE/E) in health facilities in Bauchi and Sokoto States in Nigeria.MethodsData were collected from 80 health facilities using a cross-sectional, mixed method (quantitative and qualitative) design. We assessed health facility readiness to manage PE/E and use MgSO4 as the drug of choice, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 31 publications
2
47
1
Order By: Relevance
“…Barriers to accessing MgSO 4 at facility level included inadequate supplies and perceived high costs to both health facility (e.g. costs of equipment and materials to administer and monitor MgSO 4 ) and users, which are consistent with findings in other studies …”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Barriers to accessing MgSO 4 at facility level included inadequate supplies and perceived high costs to both health facility (e.g. costs of equipment and materials to administer and monitor MgSO 4 ) and users, which are consistent with findings in other studies …”
Section: Discussionmentioning
confidence: 82%
“…costs of equipment and materials to administer and monitor MgSO 4 ) and users, which are consistent with findings in other studies. 12,14,15 Despite the fact that coverage of MgSO 4 for the prevention and treatment of eclampsia has improved, it has not necessarily translated into recommended clinical practice at different health facility levels. We found that about onequarter of all facilities were using MgSO 4 for treatment of mild pre-eclampsia, despite a lack of recommendation on such practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, women expect to receive care promptly on reaching a health facility; therefore, long waiting times present a significant challenge to accessing health facility-based services [22, 29, 31, 53, 82, 87, 97, 107, 115, 123, 154, 155]. A shortage or absence of drugs and other essential supplies in health facilities were reported in other studies [31, 48, 56, 67, 76, 111, 115, 150, 155, 157, 163, 165168], and poor referral practices/systems [104, 105, 159, 165] such as referred clients being transported unaccompanied by healthcare staff [89], lack of feedback mechanisms on referred patients [152], and late or no referral [29] hinder efficient patient care and may result in adverse outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings resonate with another study in Kenya showing gaps in provision of parenteral anticonvulsant, where 75 percent and 52 percent of providers reported administering injectable diazepam and MgSO4, respectively22 . Other studies concur with low provider competence and confidence in MgSO4 use in PE/E management5,34,35 . Staff are either reluctant to use it or administer it inconsistently with current WHO recommendations6,36,37 .…”
mentioning
confidence: 70%